Cone-beam computed tomography evaluation of bone density of midpalatal suture before, after, and during retention of rapid maxillary expansion in growing patients - Bigliazzi, Renato [UNESP] (2017)
Objective To analyze changes in bone density of the midpalatal suture after rapid palatal expansion (RME) with the Hyrax-type expander in growing subjects using cone-beam computed tomography (CBCT). Materials Fourteen patients (nine girls and five boys; mean age, 11.7 ± 2.4 years) who required RME as part of their orthodontic treatment and had preexpansion (T0) and postexpansion (at the end of active expansion [T1], after a retention period of 3 months [T2], and after 6-month [T3] retention period) CBCT scans. On the axial CBCT images, four regions of interest in the midpalatal suture were analyzed. Bone density (BD) was measured in voxel gray-scale histogram. BD measurements were compared by using Friedman ANOVA with post hoc tests. A P value less than 0.05 was considered statistically significant. Results BD values in all regions of interest in the midpalatal suture decreased significantly after active expansion (T0-T1) and significantly increased during the retention periods (T1-T2 and T1-T3). According to the density values 3 months after expansion (T0-T2), the remineralization was incomplete. At 6 months of the retention, nonsignificant differences in BD were observed in comparison with the pretreatment values (T0-T3). Conclusions Active phase of RME produced effective opening of the midpalatal suture with significant decreases in BD levels. The results revealed that are necessary more than 3 months for complete sutural recovery after RME, thus indicating in prepubertal patients, the recommendation to extend the retention time to 6 months to achieve the midpalatal suture remineralization.